2018
DOI: 10.3390/proteomes6040048
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Proteome of the Synaptic Cleft through Proximity Labeling Reveals New Cleft Proteins

Abstract: Synapses are specialized neuronal cell-cell contacts that underlie network communication in the mammalian brain. Across neuronal populations and circuits, a diverse set of synapses is utilized, and they differ in their molecular composition to enable heterogenous connectivity patterns and functions. In addition to pre- and post-synaptic specializations, the synaptic cleft is now understood to be an integral compartment of synapses that contributes to their structural and functional organization. Aiming to map … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 96 publications
(169 reference statements)
1
46
0
Order By: Relevance
“…Previous work has shown that Kcc2 is located at or in close proximity to excitatory synapses (Gulyás et al, 2001;Chamma et al, 2012;Mahadevan et al, 2017). In agreement with this we detected well characterized excitatory synapse proteins such as Cntn1 (Cijsouw et al, 2018), and Grm2/3 (Ting et al, 2016;Spence et al, 2019). Interestingly, we also identified several proteins associated with inhibitory synapses including Cacna1e (Nakamura et al, 2016), and Cyfip1 (Supplementary Table S1; Davenport et al, 2019).…”
Section: Kcc2 Is Associated With Proteins Enriched At Excitatory Andsupporting
confidence: 88%
“…Previous work has shown that Kcc2 is located at or in close proximity to excitatory synapses (Gulyás et al, 2001;Chamma et al, 2012;Mahadevan et al, 2017). In agreement with this we detected well characterized excitatory synapse proteins such as Cntn1 (Cijsouw et al, 2018), and Grm2/3 (Ting et al, 2016;Spence et al, 2019). Interestingly, we also identified several proteins associated with inhibitory synapses including Cacna1e (Nakamura et al, 2016), and Cyfip1 (Supplementary Table S1; Davenport et al, 2019).…”
Section: Kcc2 Is Associated With Proteins Enriched At Excitatory Andsupporting
confidence: 88%
“…This defect is reminiscent of the reduction in AZ length and number at perisomatic inhibitory synapses in CA1 pyramidal neurons in Tnr KO mice 62 . Together, these observations suggest that IgSF8 regulates synapse number and length, possibly via an interaction with TenR, which localizes to the excitatory synaptic cleft of cultured neurons 108 .…”
Section: Discussionmentioning
confidence: 77%
“…Intensity-based absolute quantitation (iBAQ) quantitative values of detected proteins were obtained and normalized as summed iBAQ values within one sample, which represent the molar abundance or relative iBAQ (riBAQ) of an identified protein within a sample. For each detected protein, the log2 riBAQ value was calculated (Cijsouw et al, 2018). To determine the similarity of the samples' expression profiles, a hierarchical clustering of the samples based on the correlation coefficients of the riBAQ values was performed.…”
Section: Proteomic Analysismentioning
confidence: 99%